Optimal neural network approach for estimating state of energy of lithium-ion battery using heuristic optimization techniques - Lipu M.S.H.; Hussain A.; Saad M.H.M.; Hannan M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Backpropagation algorithms; Errors; Learning algorithms; Mean square error; Neural networks; Particle swarm optimization (PSO); Torsional stress; Back propagation neural networks; Backtracking search algorithms; Heuristic optimization technique; Optimal neural network; Optimization algorithms; Particle swarm optimization algorithm; Root mean square errors; state of energy; Lithium-ion batteries